THE POLICY OF CRIMINAL LAW AGAINST THE CRIME OF PEOPLE TRAFFICKING - Intan Nurina Seftiniara (UBL, 2016)
Trafficking is a complex issue. Examples of such people is to do acts of recruitment, transportation, shelter, delivery, transfer, or receipt of a person made a threat with the purpose of exploitation. Trade this guy not only occurs in developed countries, even developing countries such as Indonesia also participate in criminal acts of trafficking people. Has been detected, the regions in Indonesia that is central to producing commercial sex workers is an area of the North coast of Central Java and East Java are very known as the granary of producing a sex worker. Criminal law policies undertaken in the prevention of criminal acts of trade people is as follows the policy formulation/application/ Policy legislation, yudiksi, execution policy/administration and basic consideration in the determination of the Criminal Verdict Taking criminal action against the Trafficking of people based on the CODE of CRIMINAL PROCEDURE and the Principal Act Power of Justice is basically the judge also refers to the judicial code of conduct, article – article that indected to the defendant that is based on Act No. 21 of 2007 about the eradication of criminal acts of Trafficking people and also upon the conscience of the judges.